Callothrix clavata development W.G.S. in soil treated with herbicide atrazine at agronomic rate - Murialdo, Raquel (2015)
Fil: Murialdo, Raquel. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.